Analisis Pengembangan Ekowisata Mangrove Kota Kendari - Murni Murni; Weka Widayati (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2022)
The potential for natural tourism, especially mangrove forests, has its own charm because it has a variety of unique natural resources, some of which are endemic, both in terms of flora and fauna. Mangrove forests if developed have a greater tourist attraction than other tourist objects. Basically mangrove ecotourism can be developed in various areas ranging from forests such as production forests, protected and conservation forests. The study used descriptive analysis, mangrove density analysis, area carrying capacity analysis, ecotourism and AHP potential assessment analysis. The results of the study show that (1) the mangrove ecosystem area located in Kendari City has the potential to be developed as a mangrove ecotourism object; and (2) The priority for developing ecotourism in the Lahundape mangrove is the ecological aspect, namely maintaining the diversity of flora and fauna by focusing on the Lahundape Mangrove on the construction of facilities and infrastructure to support reception activities in tourism and education areas, in the Bungkutoko mangrove, namely the ecological aspect, planting mangroves with an emphasis on the function of cultivation in the area with the arrangement of the mangrove area which is directly adjacent to the residents' aquaculture areas and areas where the condition of the mangrove forest has been damaged, as well as in the Anggoeya mangrove is the economic aspect, improving the community's economy by focusing on the Anggoeya Mangrove on the arrangement of the mangrove area and the seaside, namely the provision of facilities facilities that support culinary tourismfunctions.